Report of the multidisciplinary survey of the fisheries of Suriname (CARICOM Fisheries Unit Belize CityBZ, 2000)
Presents a general overview of the fisheries of Suriname, and the structure, functions and the general operations of the Fisheries Department.
Keywords: FISHERY INDUSTRY